The Effects of Coronavirus Disease-19 Pandemic on Tuberculosis Treatment Uptake and Outcomes in the Fako Division of Cameroon - Benjamin David Thumamo Pokam; Elsie Ngu Shindoh; Cecile Ingrid Djuikoue; Cedric Seugnou Nana; Sabi Hannah Kakah; Assadioh Pierre Kana Elisee; Nicholas Tendongfor (International Journal of Mycobacteriology)
Background: Tuberculosis (TB) caused by Mycobacterium tuberculosis is an infectious disease affecting mainly the lungs and persists as the leading cause of death worldwide. With the emergence of coronavirus disease-19 (COVID-19) pandemic, the management and outcome of TB has been greatly affected because of the global shift in attention. This study aims to determine the effects of COVID-19 pandemic on the TB treatment uptake and outcomes in the Fako Division of Cameroon. Methods: A hospital-based retrospective and cross-sectional study was carried out in 3 Health Districts of the Fako Division of Cameroon. Extraction forms and structured questionnaire were used to collect both quantitative and qualitative data from records and health personnel, respectively. Data on treatment uptake and outcomes before and during the pandemic were compared, as well as challenges faced in TB diagnosis and treatment during the pandemic. Results: Of the 1557 reviewed files of TB patients, treatment uptake was lower (73.40%) during compared to before (82.30%) the pandemic (P < 0.0001). A larger proportion (83.30%) had a successful outcome before compared to (74.3%) during the pandemic (P < 0.0001). There was a significant drop in both good TB treatment uptake (8.9%) and successful outcomes (9%), respectively, during the pandemic. A number of significant challenges faced in TB diagnosis and treatment during the pandemic included shortage of drugs (63.6%) and diagnostic materials (54.5%), as well as decrease in the diagnosis rate of TB patients (90.9%) with the main reason being fear of being quarantined at the hospital (63.6%). Conclusions: A decrease in TB treatment uptake and successful outcomes was observed during the COVID-19 period compared to prior the pandemic. This is indicative of poor usage of the TB services during the pandemic as a result of COVID-19 barrier measures and laxity in the TB control programs. TB programs require some intensification geared towards strengthening the patient-centered approach and a community-based active TB case finding, especially in the current potential resurgence of the pandemic.